2012
DOI: 10.1002/ajmg.a.35526
|View full text |Cite
|
Sign up to set email alerts
|

IRF6 is a risk factor for nonsyndromic cleft lip in the Brazilian population

Abstract: Nonsyndromic cleft lip with or without cleft palate (NSCL/P) is a complex disorder with a worldwide incidence estimated at 1:700. Among the putative susceptibility loci, the IRF6 gene and a region at 8q24.21 have been corroborated in different populations. To test the role of IRF6 in NSCL/P predisposition in the Brazilian population, we conducted a structured association study with the SNPs rs642961 and rs590223, respectively, located at 5' and 3' of the IRF6 gene and not in strong linkage disequilibrium (LD),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 29 publications
3
29
0
4
Order By: Relevance
“…The most significant results, persisting after Bonferroni correction, were observed when the additive model was used, confirming dosage risk effect of minor allele A. Positive association between the IRF6 rs642961 variant and nsCL/P has been confirmed by multiple studies involving various ethnicities [21][22][23][24] . Also, our results are in accordance with the findings from two case-control studies on Central European populations which showed similar magnitudes of odds ratios 10,19 .…”
Section: Discussionmentioning
confidence: 58%
“…The most significant results, persisting after Bonferroni correction, were observed when the additive model was used, confirming dosage risk effect of minor allele A. Positive association between the IRF6 rs642961 variant and nsCL/P has been confirmed by multiple studies involving various ethnicities [21][22][23][24] . Also, our results are in accordance with the findings from two case-control studies on Central European populations which showed similar magnitudes of odds ratios 10,19 .…”
Section: Discussionmentioning
confidence: 58%
“…Accordingly, AIMs have proven to be useful for inferring the putative biogeographic ancestry of individuals, estimating the ancestry proportions of admixed individuals and populations (Shriver et al 1997; Halder et al 2008; Pena et al 2011; Pereira et al 2012; Suarez-Kurtz et al 2012; Manta et al 2013), correcting case–control studies for stratification bias (Brito et al 2012a,b; Bagordakis et al 2013), and performing admixture mapping approaches. Many of such studies have benefited from AIM panels built by Brazilian research groups, focused specifically on discriminating Brazilian parental populations (Bastos-Rodrigues et al 2006; Santos et al 2010; Brito et al 2012a; Manta et al 2013). In addition, in an ethnically admixed population, it is possible to evaluate the impact of certain at-risk alleles on the occurrence of some disorders or to drug response among different ethnicities simultaneously, under similar environmental and socio-economical conditions (Suarez-Kurtz et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown common alleles in IRF6 that are associated with NSCL/P, which has been independently replicated in genome-wide association (GWA) [11], [40] and candidate gene studies [41], [42]. Animal models have also supported the role of IRF6 in NSCL/P [43], [44].…”
Section: Discussionmentioning
confidence: 86%